Association between EGF +61 G/A and glioma risk in a Chinese population - Zhang Tianbao; Qian Ji; Wu Qihan; Chen Juxiang; Fan Weiwei; Chen Hongyan; Ruan Zhenchao; Zhao Yao; Wang Shujie; Huang Yan; Lu Daru (BMC Cancer, 2010)
Abstract Background Epidermal growth factor (EGF) is critical in cancer process. EGF and EGF receptor (EGFR) interaction plays a pivotal role in cell proliferation, differentiation, and tumorigenesis of epithelial tissues. Variations of the EGF +61G/A (rs4444903) may lead to an alteration in EGF production and/or activity, which can result in individual susceptibility to brain glioma. The purpose of this study was to investigate the potential association between EGF +61G/A and brain glioma in a Chinese population. Methods In this study, we analyzed single nucleotide polymorphism of EGF +61G/A in 677 patients with glioma and 698 gender- and age-matched controls. Genotyping was performed by polymerase chain reaction-ligation detection reaction (PCR-LDR) method. Results The A allele (minor Allele) was 33.0% in cases and 27.3% in controls. The additive model was more powerful to reveal the association in our study than that of recessive and dominant model. Our data showed the genotype G/A and A/A was associated with increased risk for glioma (adjusted OR = 1.48, 95%CI: 1.17-1.87, p = 0.001 for G/A, adjusted OR = 1.81, 95%CI: 1.20-2.72, p = 0.005 for A/A, respectively), and for glioblastoma (adjusted OR = 1.51, 95%CI: 1.06-2.17, p = 0.024 and adjusted OR = 2.35, 95%CI: 1.34-4.15, p = 0.003, respectively). The A allele significantly increased glioma risk (OR = 1.31, 95%CI: 1.11-1.55, p = 0.001). The additive model (G/G vs G/A vs A/A) showed that both G/A and A/A genotype increased glioma risk (adjusted OR = 1.40, 95% CI: 1.17-1.66, p = 0.0002).G/A and A/A genotypes or EGF +61 A allele increased risk in both low and high WHO grade glioma. Non-smokers with G/A and A/A genotype showed increased glioma risk compared with G/G genotype (adjusted OR = 1.72, 95%CI: 1.29-2.30, p = 0.0002 and adjusted OR = 1.81, 95%CI: 1.10-2.99, p = 0.020, respectively). This association was not found in ever- or current-smokers. Conclusions Our study indicated that G/A and A/A genotypes or EGF +61 A allele were associated with higher glioma risk in Chinese. This is in contrast with previous studies which reported G allele as a risk factor of glioma in Caucasian. The role of EGF +61 A/G polymorphism in glioma susceptibility needs further investigation.